Atypical teratoid/rhabdoid tumor: A rare case report - Shrestha, R; Gauchan, S; Jha, A K (Journal of Chitwan Medical College, 2017)
Atypical Teratoid/Rhabdoid Tumors (AT/RTs) is rare, highly malignant embryonal tumor of central nervous system that predominantly occurs in infancy and young children. The majority of tumors arise (approximately two-third) in the posterior fossa. The diagnosis of AT/RTs relies predominantly on morphologic and immunohistochemical criteria. The most common differential diagnosis are Primitive Neuroectodermal Tumor and malignant glioma. Herein we present a case of 5 year old child who initially presented with headache and vomiting.